Socioeconomic inequalities related to perceived difficulty in accessing health services among older adults: A cross-sectional analysis of SABE Study Data. - Elaine Cristina Tôrres Oliveira; Marília Cristina Prado Louvison; Yeda Aparecida de Oliveira Duarte; Fabíola Bof de Andrade (PLoS ONE)
Analysis of trends and the magnitude of inequalities in access to health services contributes to identifying privileged groups and facilitates discussions on equity policies. Brazil has an important context for studying healthcare access inequalities due to its rapid population aging and the existence of a universal healthcare system guided by equity principles. Therefore, this study aimed to assess socioeconomic inequalities in the prevalence of difficulties accessing healthcare services among older adults living in the city of São Paulo, Brazil. This cross-sectional study used data from the Health, Well-being, and Aging Study from three years: 2006 (n = 1,386), 2010 (n = 1,319), and 2015 (n = 1,218). The dependent variable used in this study was difficulty accessing healthcare services, an outcome that aimed to assess, based on the perception of access barriers, any difficulty in using or accessing healthcare services when needed. Independent variables were socioeconomic position measured by years of education (which reflects the number of years of education completed) and monthly income (measured in minimum wages). Absolute (SII) and relative (RII) inequality indices were employed to assess the magnitude of socioeconomic inequalities. The findings indicate that individuals with higher socioeconomic status (measured by education and income) experienced lower frequencies of difficulty in accessing healthcare services. Absolute inequalities based on education and income were significant in 2006 [SII:-0.328 (-0.437; -0.220) and SII:-0.191 (-0.295; -0.087), respectively] and 2015 [SII = -0.198 (-0.314; -0.082) and SII = -0.313 (-0.425; -0.201), respectively]. Relative inequalities were significant across all study years, with difficulties in access being 68.0%, 17.0%, and 42.0% lower among individuals with higher education, and 49.0%, 22.0%, and 58.0% lower among those with higher income in 2006, 2010, and 2015, respectively. This study showed that difficulties to access were more concentrated among individuals with lower socioeconomic status, emphasizing the importance of true universalization of the healthcare system to ensure equitable access.